Evaluating Learning Management System Adoption Effectiveness for Educators and Students in Batam Higher Education - Hendi Sama; Winson Napoleon; Herman (Universitas Negeri Semarang, 2025)
The rapid expansion of digital technology and online platforms is reshaping higher education, driving widespread adoption of Learning Management Systems (LMS) and synchronous ICT tools for teaching and learning. As institutions increasingly rely on these technologies, it is essential to understand their effectiveness in supporting educational transformation rather than simply digitizing traditional practices. This study investigates the perceived integration and impact of LMS and ICT tools among students and educators across six universities, using the Technological Pedagogical Content Knowledge (TPACK) framework. A quantitative survey of 579 respondents assessed seven TPACK domains with reliable measurement instruments. Descriptive statistics, t-tests, correlation, and regression analyses were employed to compare perspectives and identify key predictors of successful technology integration. Results reveal that both groups express positive views of LMS and ICT, with all TPACK constructs rated above 3.8. Educators report higher self-assessed competencies, particularly in technological and pedagogical domains, although the differences are statistically significant but practically minor. Strong correlations among TPACK factors and regression modeling highlight Technological Pedagogical Knowledge and Technological Content Knowledge as the most important predictors of effective integration, underscoring the importance of system supported pedagogical design and content delivery rather than simple content digitization. Despite robust infrastructure and readiness, the findings suggest that LMS and ICT are primarily used to support rather than truly transform learning experiences. The study contributes to educational information systems literature by providing empirical evidence on user perceptions and the need for a system design strategies to achieve more innovative, student centric, technology‑enhanced education in Batam.